1994
DOI: 10.1093/jn/124.suppl_12.2760s
|View full text |Cite
|
Sign up to set email alerts
|

Blood Changes during Training and Racing in Sled Dogs

Abstract: Six male and six female Alaskan Huskies allocated three by three to two teams fed rations slightly different in protein/fat ratio (A, 29.2: 53.7%; B, 34.1: 48.5% of digestible energy) were studied for hematological and metabolic changes during a complete training and racing season (24 wk). Blood variables [packed cell volume (PCV), red blood cell count (RBC), mean corpuscular volume, hemoglobin, total plasma protein, free fatty acids, cholesterol, lactic acid, creatine phosphokinase (CPK), creatinine, alanine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
30
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 5 publications
6
30
0
Order By: Relevance
“…Currently, field studies of dogs performing specific activities and reported in the veterinary literature include investigations of sled dogs (Hinchcliff et al, 1993(Hinchcliff et al, , 1997Querengaesser et al, 1994;Burr et al, 1997;Baskin et al, 2000;Piercy et al, 2000Piercy et al, , 2001aPiercy et al, , 2001bDunlap et al, 2006;McKenzie et al, 2007;Angle et al, 2009;Wakshlag et al, 2010) and Greyhounds (Lassen et al, 1986;Snow et al, 1988;Ilkiw et al, 1989;Rose and Bloomberg, 1989;Nold et al, 1991;Pieschl et al, 1992). These two groups represent large, accessible populations of canine athletes that are often relatively uniform in age and genetic background, and the studies demonstrate that important changes do occur in the exercising canine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, field studies of dogs performing specific activities and reported in the veterinary literature include investigations of sled dogs (Hinchcliff et al, 1993(Hinchcliff et al, , 1997Querengaesser et al, 1994;Burr et al, 1997;Baskin et al, 2000;Piercy et al, 2000Piercy et al, , 2001aPiercy et al, , 2001bDunlap et al, 2006;McKenzie et al, 2007;Angle et al, 2009;Wakshlag et al, 2010) and Greyhounds (Lassen et al, 1986;Snow et al, 1988;Ilkiw et al, 1989;Rose and Bloomberg, 1989;Nold et al, 1991;Pieschl et al, 1992). These two groups represent large, accessible populations of canine athletes that are often relatively uniform in age and genetic background, and the studies demonstrate that important changes do occur in the exercising canine.…”
Section: Introductionmentioning
confidence: 99%
“…At the other end of the athletic spectrum, sled dogs exhibit changes related to prolonged exercise, including increased blood volume resulting in decreased packed cell volume due to hemodilution (Querengaesser et al, 1994;Burr et al, 1997). This change does not result in a decrease in total erythrocyte number, but rather reduces cardiac load due to diminished blood viscosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted in order to assess these modifications associated with exercise in racing Greyhounds [12], Sled dogs [10], labrador dogs during retrieving exercises [6,23] and in dogs of different breeds during agility competitions [19,20]. the authors have demonstrated that training and racing cause physical and mental stress as in human athletes [15]. the evaluation of these variations it is of the utmost importance to understand which metabolic pathways are involved, and which physiological adaptations are induced by different types of exercise [1].…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of these changes is essential in order to design specific and individual training protocols, for an early diagnosis of lack of performance, to assess the impact of different feeding or supplementation strategies and to minimize the risk of exerciselinked diseases, such as exertional rhabdomyolysis, exhaustion, dehydration, heat stroke and electrolyte imbalances within others. In this way, several researchers have been conducted in order to assess the modifications associated with exercise in racing Greyhounds (Lassen et al, 1986;Snow et al, 1988;Ilkiw et al, 1989;Rose and Bloomberg, 1989;Nold et al, 1991), sled dogs (Querengaesser et al, 1994;Hinchcliff et al, 1993Hinchcliff et al, , 1998Burr et al, 1997;McKenzie et al, 2007), Labrador dogs during retrieving exercises (Matwichuk et al, 1999;Steiss et al, 2004) and in dogs of different breeds during Agility competitions (Rovira et al, 2007a,b).…”
mentioning
confidence: 99%